EFEKTIFITAS MODEL FLIPPED CLASSROOM DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA PADA PEMBELAJARAN DARING/HIBRIDA - Rahayu Rahmadani; Efna Yulita; Sinta; Ena Suma Indrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of online and hybrid learning requires students to have a high level of learning independence to be able to manage the learning process effectively and sustainably. However, various studies show that student learning independence in Indonesia is still relatively low, mainly due to online learning which tends to be oneway and less student-centered. One learning model deemed relevant to address this challenge is the flipped classroom, as it provides a structured, independent learning space through pre-class activities and synchronous learning oriented towards deepening concepts. This study aims to comprehensively examine the effectiveness of the flipped classroom model in improving student learning independence in online and hybrid learning. This study used a qualitative approach with a literature review method of various relevant primary and secondary literature sources, including articles from accredited national journals, scientific proceedings, reference books, and education policy documents. Data analysis was conducted using content analysis techniques combined with thematic synthesis to identify patterns of findings, indicators of learning independence, and supporting and inhibiting factors in the implementation of the flipped classroom. The results show that the flipped classroom is consistently able to improve student learning independence, as reflected in increased learning initiative, academic responsibility, time management, self-regulation, and self-reflection and self-evaluation skills. Compared to conventional online learning, flipped classrooms are more effective in encouraging active student engagement and reducing reliance on teachers. With careful pedagogical planning and adequate technological support, flipped classrooms have the potential to be an adaptive and sustainable learning strategy for strengthening independent learning in the digital education era.